(untitled) (Circe de clásicos y modernos, 2018)
This article compares the compositional sequences of the Jean Anouilh’s Antigone in relation with the homonym Sophoclean play. Convergences and divergent aspects between the protagonists and secondary characters of both plays are analyzed and also the role of the Chorus is mentioned. Finally conclusions are presented, highlighting the fundamentalist tone which Creon acquires at the end of the play.